Can Squat Jump Performance Differentiate Starters vs. Nonstarters in Division I Female Soccer Players?. Issue 8 (August 2018) - Magrini, Mitchel A.; Colquhoun, Ryan J.; Sellers, John H.; Conchola, Eric C.; Hester, Garrett M.; Thiele, Ryan M.; Pope, Zach K.; Smith, Doug B.
Abstract : Abstract: Magrini, MA, Colquhoun, RJ, Sellers, JH, Conchola, EC, Hester, GM, Thiele, RM, Pope, ZK, and Smith, DB. Can squat jump performance differentiate starters vs. nonstarters in division I female soccer players? J Strength Cond Res 32(8): 2348–2355, 2018—Although soccer is predominately an endurance sport, high velocity movements may be an important indicator of athletic success. The purpose of this investigation was to establish whether squat jumps (SJs) can differentiate starters from nonstarters with a female collegiate division I soccer team. Eighteen female division I soccer athletes were separated into 2 groups: 9 starters (age: 19.5 ± 1.0; mass = 64.8 ± 11.5 kg; height = 167.5 ± 7.7 cm; games started = 18.2 ± 4.7; and minutes played = 1633.8 ± 478.2 minutes) and 9 nonstarters (age: 19.4 ± 1.4 years; mass = 63.3 ± 4.2 kg; height = 164.7 ± 6.8 cm; games started 0.7 ± 1.3; and minutes played 158.2 ± 269.3 minutes). Each athlete performed 3 maximal SJs at a starting knee angle of 110° without arm swing. Each participant's SJ height, mean power (MP), peak power (PP), mean velocity (MV), and peak velocity (PV) were measured during each attempt by a linear position transducer. No statistically significant differences ( p ≥ 0.05) in MP and PP between the starters and nonstarters were observed. However, starters performed significantly better than nonstarters in SJ height ( p = 0.002), MV ( p = 0.025), and PV ( p = 0.015). In addition, SJ height was strongly correlated with MV ( r = 0.628) and PV ( r = 0.647). These findings suggest that SJ height, MV, and PV may be important variables for discriminating differences between starters and nonstarters in division I female soccer athletes and a strong indicator of explosive performance.